Regional party elites: from the son of a nomad to the head of the national republic (early 1960s–late 1970s) - E. N. Badmaeva; E. U. Omakaeva (Nomadic Civilization: Historical Research)
Within the framework of the presented publication, on the materials of Kalmykia, the process of the formation of the Soviet regional party-political elite in the early 1960s–late 1970s is described in detail. On the example of the image of B.B. Gorodovikov, some touches to the associative image of the son of a nomad, who rose from farm laborer to lieutenant general and leader of the Kalmyk Autonomous Republic, are considered. In the difficult period of reconstruction of the socio-economic structure of the republic, which decisively changed military service in the Soviet army to a regional managerial position, after the illegal deportation of the Kalmyk people to Siberia, becoming the first leader of Kalmykia of the titular nationality. The aim of the presented work was to study the mechanism of the formation of the regional party-political elite in the early 1960s–late 1970s, to which it is customary to refer the secretary corps of the Communist Party committees in the regions. This study is relevant based on the need to improve the system for the selection and training of qualified management personnel at the level of individual regions. This, in turn, motivates the research search of scientists in the field of personnel policy of previous historical periods. The importance and timeliness of the stated problems is largely due to the strategically important positions that are occupied by leading management personnel in the social and social structure of Russian society. At the same time, the study of Soviet management experience is very important in the implementation of modern personnel policy. In addition, the study will make it possible to fill in some historiographic gaps and provide an opportunity to analyze Soviet nomenclature practices. The scientific novelty of the presented article is determined by the fact that certain elements in the practice of forming a regional party-political elite in the early 1960s and late 1970s. described in the complex. At the same time, such studies on Kalmyk material have not been carried out before, which makes it possible to introduce into scientific circulation a number of previously unpublished sources.